2007
DOI: 10.1590/s0100-83582007000200011
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da área foliar de cinco espécies do gênero Amaranthus usando dimensões lineares do limbo foliar

Abstract: RESUMO -Este trabalho foi realizado com o objetivo de obter equações que estimem a área foliar de espécies de plantas daninhas do gênero Amaranthus utilizando as dimensões lineares do limbo foliar, bem como comparar as equações obtidas para plantas que cresceram em casa de vegetação e em campo. Para isso, plantas de A. deflexus, A. hybridus, A. retroflexus, A. spinosus e A. viridis foram cultivadas em casa de vegetação ou coletadas em infestações naturais de áreas agrícolas e não-agrícolas do município de Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
(14 reference statements)
0
8
0
5
Order By: Relevance
“…All equations had coefficients of determination above 90%; however, among the 12 sowing dates, only eight were similar to the general model (Table 3). In this case, the models were compared by analyzing the overlap of the confidence interval (Carvalho & Christoffoleti, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…All equations had coefficients of determination above 90%; however, among the 12 sowing dates, only eight were similar to the general model (Table 3). In this case, the models were compared by analyzing the overlap of the confidence interval (Carvalho & Christoffoleti, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The equations are considered equivalents when the confidence intervals are overlapped (CARVALHO; CHRISTOFFOLETI, 2007), so that the regression analyses must be processed separately if the overlapping do not occurred.…”
Section: Thismentioning
confidence: 99%
“…This non-destructive, easy and quick method for leaf area estimation is important for plant growth evaluation in field conditions (BIANCO et al, 2007). The relationship between the real leaf area and the linear measures of leaves had been studied successfully for weed leaf area determination based on regression analysis by Carvalho and Christoffoleti (2007), Bianco et al (2007), Bianco et al (2008a and b) and others.…”
Section: Introductionmentioning
confidence: 99%
“…A generalized leaf area equation LA = α × L × W for maize plants was proposed by Montgomery, (1911), based on a rectangle area L × W (L -leaf length, W -leaf width) and on a weighing factor (α) equal to 0.75. However, several authors indicated that the weighting factor may vary depending on the maize variety (Bange et al, 2000;Carvalho and Christoffoleti, 2007;Tivet et al, 2001), plant development stage (Bange et al, 2000), environmental conditions and agronomic practices (Elings, 2000;Sezer et al, 2009). Therefore, application of this classic equation requires a measurement of length and width of all leaves on a plant, which is very labour and time consuming, and can be a source of errors.…”
Section: Introductionmentioning
confidence: 99%